Near-Infrared-II Bioimaging for in Vivo Quantitative Analysis - Yang, Sha; Tan, Xiaofeng; Tang, Li; Yang, Qinglai (Frontiers in Chemistry, 2021)
Near-Infrared-II (NIR-II) bioimaging is a newly emerging visualization modality in real-time investigations of biological processes research. Owning to advances in reducing photon scattering and low tissue autofluorescence levels in NIR-II region (1000-1700 nm), NIR-II bioimaging affords high resolution with increasing tissue penetration depth, and it shows greater application potential for in vivo detection to obtain more detailed qualitative and quantitative parameters. Herein, this review summarizes recent progresses made on NIR-II bioimaging for quantitative analysis. These emergences of various NIR-II fluorescence, photoacoustic (PA), luminescence lifetime imaging probes and their quantitative analysis applications are comprehensively discussed, and perspectives on potential challenges facing in this direction are also raised.